Synthesis and Structure of a Three-Dimensional Mn(COO)3 Anionic Framework - Jiang, Zhiqiang (Asian Journal of Chemistry, 2012)
Manganese-crystallization of formic acid from the decomposition of N,N-dimethylformamide solvent was synthesized and characterized by single-crystal X-ray diffraction. This compound crystallized in a hexagonal space group of R-3c with a = b = 8.3319(5) Å, c = 22.851(2) Å, a = b = 90.00º, l = 120.00º, V = 1373.81(17) Å3 and Z = 2. This compound possessed 6-connected three-dimensional Mn(COO)3 anionic framework.